Nutrient limitation of phytoplankton growth in the freshwater tidal zone of a turbid, Mediterranean estuary - Domingues, Rita B. (2012)
Identification of the limiting nutrient(s) is a requirement for the rational management of eutrophication. Here, we present the first experimental analysis of nutrient limitation of phytoplankton growth and its seasonal variation in the Guadiana estuary (SE Portugal-SW Spain). Ten microcosm experiments were performed during 2005 and 2008, using water samples collected in the freshwater tidal zone of the Guadiana estuary. Nitrate, phosphate and silicate were added in a single pulse, alone and in combinations. Experimental treatments were incubated for 4 days under controlled laboratory conditions. Phytoplankton response to nutrient enrichment was evaluated through changes in biomass (Chla), and abundance of specific phytoplankton groups. Overall, phytoplankton growth seemed to be nitrogen-limited throughout the productive period, especially green algae in 2005 and diatoms in 2008. In the summer 2008, cyanobacteria and the harmful dinoflagellate Kryptoperidinium foliaceum responded to N enrichment in the absence of Si. Indeed, the presence of K. foliaceum was observed for the first time in the freshwater tidal reaches of the Guadiana estuary, where dinoflagellates were usually absent or rare. The significant increase on dinoflagellates and cyanobacteria growth in response to N enrichment in the absence of Si is alarming, because anthropogenic nutrient enrichments usually increase N and P, but not Si. Furthermore, relatively high N concentrations, up to 22 mM, were found to be limiting to phytoplankton growth. These results should therefore be used as a management tool when establishing nutrient criteria and nutrient loading budgets to estuarine waters.